Readiness of Nurses and Nursing Students to Use Artificial Intelligence in Healthcare and Influencing Factors - Aktura, Seher Çevik; Dertli, Semiha (My University, 2026)
Objective: The acceptance and efficient implementation of artificial Intelligence (AI)-based applications in routine nursing activities depends on readiness towards artificial intelligence. This study aims to explore nurses' and nursing students' knowledge, opinions, and attitudes towards artificial intelligence and the factors that influence them. Material and Method: The analytical cross-sectional study was conducted between March and May 2022, with 580 participants, including nurses (217) and nursing students (363) in a city in eastern Turkey. The data was collected using the “Information Form for Personal Details and Artificial Intelligence Knowledge of Nurses and Students” and the “Medical Artificial Intelligence Readiness Scale for Medical Students (MAIRS-MR)”. Results: This study showed that 46.1% of nurses and 34.4% of nursing students did not know how to use artificial intelligence in nursing. Both nurses and nursing students’ sources of information regarding artificial intelligence in nursing were essentially “social media” and the application they mostly associated the concept of artificial intelligence with was “robots”. More than half of nurses and students were curious about using artificial intelligence in nursing care. The nurses’ and nursing students’ mean MAIRS-MR scores were 67.17±18.19 and 69.41±15.18, respectively. Conclusion: The study demonstrated that nurses and nursing students had a moderate level of readiness for medical artificial intelligence. Keywords: Artificial intelligence, nurse, nursing student, readiness.
Keywords: Nurse; artificial intelligence; nursing student; readiness